(untitled) (Research, Society and Development, 2022)
Addressing the importance of running as a prevention and promotion strategy mental health is of great relevance due to the large number of people with mental disorders. The present study aims to highlight the impacts of running in promoting of the mental health of runners through the reports of these subjects. It is a qualitative, exploratory, descriptive, analytical research. For data collection, semi structured interviews were carried out, the inclusion criteria used were, who practice the sport regularly for more than 1 year, aged between 24 and 65 years and the free will to participate in the survey. The data were submitted to content analysis in the modality Minayo’s theme, which comprises: ordering, classification and final analysis of the data. After analysis of the empirical material, it was possible to identify the main mental disorders reported by runners and the impacts of running on mental health. Among the research participants, the majority reported that they feel or have already felt some symptoms of anxiety and/or depression. in what if regarding the mental health impacts after the race, 100% of the participants reported major changes, such as the reduction or disappearance of symptoms of mental disorders. Participants also reported positive impacts on self-esteem, search for more health, in addition to discipline, greater productivity, physical and emotional well-being and improved sleep, mood etc. It is concluded that the practice of running generates great impacts on mental health of runners portraying it as a prevention and health promotion strategy mental.